Preparing the Next Generation of Health and Physical Educators through Trauma-Informed Programs. Issue 9 (21st November 2020) - Ellison, Douglas; Wynard, Tammy; Walton-Fisette, Jennifer L.; Benes, Sarah
Abstract : As Physical Education Teacher Education and Health Education Teacher Education faculty members, it is essential to help our students acquire the skills to handle the traumas/stress in their lives. It is also important to provide appropriate pedagogical practices so they are prepared to support the P–12 students they will eventually teach as they will have their own adversities they are navigating. For those students in P–12 who are trying to survive and function in the world, because they have experienced trauma and toxic stress, learning can be challenging. Therefore, Physical Education Teacher Education and Health Education Teacher Education programs must prepare their students to be able to create pedagogical spaces that are trauma informed/trauma invested to meet the needs of today's P–12 students. Therefore, in this article, we provide resources, strategies, and activities to guide instructors about content and pedagogical practices related to trauma. Physical Education Teacher Education and Health Education Teacher Education will be presented separately, as their contexts and content are different, although information on trauma and toxic stress can be applied to both programs.